SENTENCE PATTERN ANALYSIS OF ACTIVE AND PASSIVE CONSTRUCTIONS IN A NEWS ARTICLE: A TRANSFORMATIONAL–GENERATIVE GRAMMAR PERSPECTIVE ON “DEADLY STROMS RAVAGE ASIA, KILLING MORE THAN 600” - Devi meilia permata sari; Aisyah Kusuma Wardani; Abdul Syukur; Sigit Wibowo; Eny Maulita Purnama Sari (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2026)
Abstract: This study uses Noam Chomsky's Transformational–Generative Grammar to examine phrase patterns in a news item, with an emphasis on the distribution of active and passive constructs at the surface structure level. The information came from an Egypt Independent news item headlined